2017
DOI: 10.3389/fncel.2017.00298
|View full text |Cite
|
Sign up to set email alerts
|

Laser Speckle Imaging of Rat Pial Microvasculature during Hypoperfusion-Reperfusion Damage

Abstract: The present study was aimed to in vivo assess the blood flow oscillatory patterns in rat pial microvessels during 30 min bilateral common carotid artery occlusion (BCCAO) and 60 min reperfusion by laser speckle imaging (LSI). Pial microcirculation was visualized by fluorescence microscopy. The blood flow oscillations of single microvessels were recorded by LSI; spectral analysis was performed by Wavelet transform. Under baseline conditions, arterioles and venules were characterized by blood flow oscillations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The range of vasomotor activity can be further divided into shorter intervals depending on the vasomotor origin. T. Mastantuono et al reported earlier that in the rat brain, oscillatory patterns characterize pial blood flow and the pial circulation of rats is regulated by the same mechanisms as the microcirculation of the human skin [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of vasomotor activity can be further divided into shorter intervals depending on the vasomotor origin. T. Mastantuono et al reported earlier that in the rat brain, oscillatory patterns characterize pial blood flow and the pial circulation of rats is regulated by the same mechanisms as the microcirculation of the human skin [52].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, relative myogenic reactivity increases with decreasing vessel diameter, which is most likely what we have seen in our work. However, the physiological significance of the myogenic range in the regulation of cerebral blood circulation is still under discussion [3,52]. The origin of such signals in cerebral microcirculation is not definitively clear, and separating the effect of blood pressure fluctuations from vasomotor dynamics on cerebral hemodynamics is an unresolved problem [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reliable assessment of NVC is only possible with proper surgical window preparations, stable animal physiology, reliable and reproducible stimulation modalities, precise data acquisition, and objective image analysis algorithms (38). One of the gold standard techniques for NVC measurements is LSCI which is a simple, non-invasive in vivo imaging technique for the measurement of tissue perfusion (39)(40)(41)(42)(43). When moving objects are illuminated by dispersed laser light, the scattered light will form an interference ("speckle") pattern, which is proportional to tissue perfusion (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…(Sigma-Aldrich, Milan, Italy) and maintained with supplemental injections (α-chloralose 30 mg/kg b.w., i.v.). They were tracheotomized and mechanically ventilated ( Mastantuono et al, 2017 ). Subsequently, the right and left common carotid arteries were isolated to induce hypoperfusion by clamping (BCCAO).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Moreover, the values of respiratory CO 2 and blood gases were recorded and maintained stably within physiological ranges. A closed cranial window prepared above the parietal cortex ( Ngai et al, 1988 ) was used to observe the pial microcirculation after the removal of the dura mater as reported previously in detail ( Mastantuono et al, 2017 ).…”
Section: Surgical Proceduresmentioning
confidence: 99%